Workplace safety drivers: Strategic insights into communication, procedure, infrastructure, leadership & emergency procedure - S, Sothivanan.; K, Manikandan.; E, Nakkeeran. (Edelweiss Applied Science and Technology, 2025)
Workplace safety is a notion that derives from research on high-reliability organizations. The possibility of physical injury, whether immediate or gradual, to people, property, or the environment while they perform their duties is a feature of work systems. We explained the main strategies and advancements to achieve no accidents in the workplace. It acts as the foundation for building a strong safety structure that protects the health and safety of those engaged in hazardous oil, chemical, and gas industries. Here, our work emphasizes obtaining and maintaining Safety Integrity Level (SIL) ratings in accordance with Indian and international standards to reduce hazardous gas leaks and implement security measures. We also discussed the statistical techniques of workplace safety and its factors, such as strategic insights into communication, procedures, infrastructure, leadership, and emergency procedures. We used five distinct manufacturing and healthcare-based industries for comparison. Company 4 has a high mean in incident awareness and communication (3.46±0.21). Company 5 has a high mean in risk assessment and hazard identification. Company 1 has a high mean in training and competency, including emergency response and incident reporting. It also explains how safety-conscious companies can lower workplace accidents through the use of emergency response, incident communication, and safety management techniques.